دراسة الهامش التسويقي والكفاءة التسويقية لزيت الزيتون المسوق في محافظة اللاذقية - جحجاح محسن (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى دراسة الهامش التسويقي، والكفاءة التسويقية لزيت الزيتون، وحسابها للموسمين الزراعيين 2006-2007 موسم إنتاج،2007-2008 موسم معاومة، من خلال دراسة أسعار البيع من المنتجين وتكاليف الوظائف التسويقية والإنتاجية التي تؤدى على المنتَج (زيت الزيتون) خلال المسلك التسويقي، حققت الهوامش التسويقية (المطلق، والنسبي، ومعدل الزيادة السعرية) لحلقة المستهلكين المحليين المرتبة الأولى بين الحلقات المدروسة مسجلة (90.17 ل.س، 51.71%، 107.08%) على الترتيب، في موسم الإنتاج، (65.02 ل.س،29.9%،42.66%) على الترتيب في موسم المعاومة. وازدادت الكفاءة التسويقية في موسم المعاومة عنه في موسم الإنتاج الجيد وفق المؤشر الأول لجميع أنواع الزيوت الممتاز والجيد وشبه الجيد مسجلة على الترتيب في موسم المعاومة (85.93، 81.86، 83.04)%، وفي موسم الإنتاج (83.91، 73.20، 72.21) %، أما وفق المؤشر الثاني فنلاحظ ارتفاع الكفاءة التسويقية في موسم الإنتاج مقارنة بموسم المعاومة مسجلة (24.97، 14.64، 14.86) %، في موسم الإنتاج،(5.01، 0.03، 3.02)% في موسم المعاومة للزيت الممتاز، والجيد، وشبه الجيد على الترتيب. The research aimed to estimate olive oil marketing margin and marketing efficiency for two seasons, (2006- 2007) production season and (2007- 2008) alternate season. It involved studying sales prices, as provided by from producers, and the costs of marketing and production functions of olive oil throughout the whole marketing process, because of their great importance as indicators of the marketing process success. Marketing margin and marketing efficiency are the most important parameters of the marketing process success. The marketing margins (absolute, relative, and average increase) of the local consumers’ circle achieve the first place among the studied circles recorded in order (83.04 s.p, 81.86%, and 85.93%) in the production season, and (65.02 s.p, 29.9, and 42.66 %) in the alternate season. The marketing efficiency increases in the alternate season more than in the production season, according to the first parameter of all oil kinds (extra virgin, virgin, and ordinary) recorded in order as (83.04 ،81.86, and 85.93)%. The second parameter referred to the increase of the marketing efficiency of all oil kinds (extra virgin, virgin, and ordinary) recorded in order as (24.97, 14.64, and 14.86) % in the production season, and (5.01, 0.03, and 3.02) % in the alternate seasons.